Exploring the relationship between course pedagogy and learning in workplaces: the case of the National Diploma in Environmental Education Training and Development Practice - Misser, Shanu (Rhodes University, Faculty of Education, Department of Education, 2017)
This case study research provides insights on course pedagogy in the National Diploma in Environmental Education Training and Development Practice as registered with the South African Qualifications Authority. The study draws its findings from interviews, observations, and document analysis of course materials and workshop processes. The two case studies of employees working in a municipal and a provincial context in South Africa provide rich insights into workplace practices and its implications for pedagogical approaches in work-integrated courses. The role of scaffolding, reflexivity and situated learning in creating learning experiences that learners have a reason to value emerge as significant approaches to be considered in pedagogy for work-integrated courses. Critical open-ended questions supported by course material design, dialogue, participation in cooperative learning situation underpinned by reading and the use of case studies and real situated experiences emerge as important pedagogical approaches enabling scaffolding and reflexivity to support a "critical mode of being" . The significant role of pedagogical approaches in maintaining relevance to workplace practices are seen as important in developing capabilities of participants to value what they do on courses. Linked to the insights gained from this study three important recommendations are made. The first recommendation suggests that a pedagogical approach, which involves learner-practitioners and workplace representatives in the curriculum design, would help to maintain relevance of the assignments to the workplace. The second recommendation suggests creative and innovative pedagogical approaches to capture workplace practices in real authentic and meaningful situations for assessment. The third recommendation suggests that pedagogies used in workplace courses need to consider social-ecological sustainability competencies that transgress job tasks across occupations which foster appreciation and imagination of new possibilities in the work learner-practitioners engage in.
Keywords: National Diploma in Environmental Education Training and Development Practice; Environmental education -- South Africa; Occupational training -- South Africa